STUDY ON THE ADDITION OF REBON SHRIMP PROTEIN HYDRAULICATE (Acetes sp.) INTO THE PURPLESWEET POTATO (Ipomoea batatas L. Poir) MODIFIED FLOUR - Sukma, Elni; Suparmi, Suparmi; Buchari, Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTÂ Protein hydrolyzate is a product resulted from the breakdown of simple peptides and amino acids through the hydrolysis process by enzymes, acids or alkalis. The purpose of this study was to determine the effect of the addition of modified purple sweet potato flour (Ipomoea batatas L. Poir) into therebon shrimp protein hydrolyzate (Acetes sp.). The research method was an experiment using a non-factorial Completely Randomized Design (CRD) to compose and conduct 4 treatments of varied flour compositionadded (0%, 5%, 10%, and 15%). The parameters used to assess the quality of the modified flour produced were sensory evaluation (appearance, consistence, aroma, and texture) and the proximate composition. The results showed that the addition of shrimp protein hydrolyzate had a significant effect on the purple sweet potato flour. The best treatment was shown by the addition of 15% shrimp protein hydrolyzate, characterized by the dark purplein appearance, less attractive, intact, less neat and dry texture, very smooth, compact and produces a very fragrant aroma specific to rebon shrimp. The best product was shown by the scoreof the consistence 6.1; the aroma 7.1; and the texture8.1; meanwhile the proximate composition was shown by the content of water 6.31%; ash 4.02%; fat 0.84%; protein 16.54%, and carbohydrates 72.28%. The quality of the product was appropriate to Indonesian Quality Standard required forsweet potato flour.Â Key words: modified flour, protein hydrolyzate, sweet potato,rebon shrimp